Long-term macroeconomic modelling of the Bulgarian economy to analyse the effects of anticipated changes in the energy sector - Andreas Bockermann; Norbert Molitor; Marc Ingo Wolter; Jürgen Blazejczak (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2006)
The middle and long-term forecasts of the economy for transition countries is an important challenge in order to understand better the effects of anticipated changes. During the accession negotiation between Bulgaria and the EU the continuation of the Kozloduy Nuclear Power Plant was a major stake both for Bulgaria and for the EU, such that various different options have been intensively discussed. In order to establish a transparent and factual basis different aspects have been analysed among which the consequences of the energy sector, in the local and over-regional economy, in social and environmental aspects. During the process of analysis it appeared appropriate and useful to analyse in-depth also the complex effects on the macro-economy of Bulgaria. In particular, negative and positive effects triggered in sectors others than the energy sector was to be evaluated. For this purpose a macroeconometric model INFORBG of the Bulgarian economy was developed. The model is disaggregated into 14 economic sectors. It represents the system of national accounts and describes the interdependent developments of some 250 macroeconomic variables. Thus it permits to set up consistent quantitative scenarios. In order to assess the macroeconomic consequences of an early closure two scenarios - one describing a deferred closure and the other one describing an early closure - were compared with each other. The model and its calculation results demonstrated a good example for practical use of macro-economic models in analysing anticipated changes in the economy of transition countries.
Keywords: E22; D78; Q43; 330; MACRO ECONOMIC MODEL; Bulgarian Economy; Effect; Energy Sector; anticipated changes